Manajemen Mutu Perguruan Tinggi: Studi tentang Kepemimpinan Visioner terhadap Kinerja Dosen dan Mutu Perguruan Tinggi di STIA Muhammadiyah Selong - Nova Hari Santhi; Salmi Yuniar Bahri (Pusat Riset dan Inovasi Nasional, 2025)
The objectives of this study were (1) to test the effect of visionary leadership on lecturer performance, (2) to test the influence of visionary leadership on higher education quality, (3) to test the effect of lecturer performance on university quality. (4) Testing the effect of visionary leadership indirectly on the quality of higher education through Lecturer Performance.This research is a type of causality research, namely cause and effect research. The population in this study were all elements at STIA Muhammadiyah Selong (lecturers, administrative staff, leaders and students) so the total population was 500 respondents. The sample in this study were 222 respondents who were taken using proportionate statified random sampling technique, which is taking samples that have the same strata. Data collection using a questionnaire or questionnaire method. A questionnaire method or questionnaire is used to get respondents' responses regarding service quality, employee performance and student satisfaction. The data analysis used to test the hypothesis in this study is to use the Structural Equation Model (SEM) analysis included in the AMOS v program. 22.The results showed that there was a positive and significant influence between visionary leadership on lecturer performance, visionary leadership had a significant effect on quality management, lecturer performance had a significant effect on quality management. The direct effect is greater in value than the indirect effect. Therefore the lecturer performance variable is a variable that cannot be a mediating variable in this study. Therefore, it is necessary to add another variable as a mediating variable in this Study.